Urgensi Perluasan Kewenangan Hakim untuk Memberikan Perintah Penetapan Tersangka Melalui Praperadilan - Jennifer Editha; Syarif Nurhidayat (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
Determination of suspects has an important role in the scope of criminal law in Indonesia because this stage aims to find material truth. The rights of suspects are fundamental rights because they relate to deprivation of a person's independence, so that the state is obliged to protect these rights from potential abuse of power by law enforcement officials during the legal process. This study aims to examine the urgency of expanding the authority of pretrial judges in ordering the determination of suspects by law enforcement officials based on legal considerations by judges in pretrial decisions number 24/Pid.Pra/2018/PN.Jkt.Sel and the Indonesian criminal justice system. Research is reviewed using normative methods which are analyzed through statutory and conceptual approaches. The results of the research show that first, in his consideration the judge has exceeded his authority because the decision has entered the subject matter. Second, based on philosophical, sociological and juridical foundations, there is no urgency to expand the authority of pretrial judges. Philosophically, pretrial is limited to examining formal law. Sociologically, the expansion of authority has the potential to lead to the arbitrariness of judges in determining a person's legal status. Juridically, the order to determine the suspect has exceeded the authority of the pretrial judge.